INSTITUTIONAL FRAMEWORK OF COLLECTIVE CONSUMER PROTECTION IN THE REPUBLIC OF SERBIA: CONDITION AND PERSPECTIVES - Popovic, Jovana (Pravni zapisi, 2021)
The paper presents the system for protection of consumers’ collective interests in the Republic of Serbia and its development perspectives. The paper relies on certain results of the research conducted at the Union University School of Law, as well as on specific comparative legal approaches. The Law on Consumer Protection introduced an administrative procedure for collective consumer protection. Contended arguments in favour of that change were efficiency and low costs of administrative procedure. In practice, administrative protection has proven to be more effective than judicial protection, but the effect of deterring traders from actions that violate consumer rights has not been fully achieved. In that sense, the existing system of protection of consumers’ collective interests in Serbia can be improved by modifying certain administrative measures and by introducing specific forms of alternative dispute resolution in Serbian consumer legislation. The novelties brought by the Directive on Representative actions, whose adoption can be expected very soon, have also been presented in the paper.
Keywords: consumer; protection of collective interests of consumers; administrative procedure; forms of alternative dispute resolution